Aktualisasi Integritas Etika Jaksa Dan Konsekuensinya Terhadap Profesi : (Analisis Kasus Terlibatan Jaksa Dalam Praktik Tambang Ilegal Di Konawe Utara, Sulawesi Tenggara) (International Forum of Researchers and Lecturers, 2024)
The prosecutor as the trial supervisor (Dominus Litis) has a central position in legal protection, because according to the Criminal Procedure Code, only the prosecutor can decide whether a case can be brought to court or not. The prosecutor's space for movement is controlled by a rule that binds the profession, namely the Code of Ethics. Integrity is one of the important things in the contents of the Prosecutor's professional code of ethics. Where a prosecutor needs to have consistency and firmness in upholding noble values ​​and beliefs. Because honest law enforcers will gain trust.